The Crown Witnesses Objectivity in Evidence System of Indonesian Criminal Law - Yahman; Prasetyo, Dossy Iskandar; Rosmaya, Ina; Hidayat, Ahmad; Kunarso; Hakiki, Azizul (Acta Universitatis Danubius. Juridica, 2023)
In criminal case, defendants who jointly commit a criminal act can be used as witnesses between one another, called crown witnesses. The function of witnesses in every criminal case is very crucial since their statement are able to determine the judge's decision, which every witness statement always has great attention both by the legal actors involved in the trial and by legal observers. This research is normative juridical research through a statutory case approach to find out whether the presence of a crown witness is not contrary to the objectives of the law and how the legal protection of crown witnesses in corruption crimes.